Kinetic Investigations of Nickel and Iron Complexes with Olefinic and Macrocyclic Ligands - Ritz, Florian Josef; Justus Liebig University Giessen (My University, 2023)
Catalytic reactions with widely available and low-cost transition metals are among the important building blocks of the modern chemical industry with its thousands of products. Most of these however can be traced back to a limited number of basic reactions. The detailed study of these reactions in fundamental organometallic research is therefore at the beginning of the process chain in order to understand the ideal conditions for the catalytic conversions. Furthermore, an increase in efficiency and cost optimization is always in focus, which can be achieved by cheaper and more efficient catalysts or adapted reaction conditions at low pressures and temperatures. Detailed mechanistic investigations can be carried out, for example, by spectroscopic methods at low temperatures, so that equilibrium constants can be determined for wide temperature ranges and basic reaction parameters and mechanisms can be derived. In Chapter 3 the reactions of nickel(0) precursors and an isoelectronic copper (I) precursor with novel cyclopropane-containing olefinic and acetylenic ligands were investigated and kinetic measurements via stopped-flow UV-vis spectroscopy were performed at various temperatures. In the mechanistic studies with the ligand bicyclopropylidene (bcp) an associative or associative interchange mechanism with an ordered transition state could be shown as the basis of the conversion. Reactions with the ligand dicyclopropylacetylenes (dcpa) were also performed in comparison and a structural study of the complexes with nickel and copper and description of features of the molecular structures were carried out. The obtained results of the structural analyses were further compared with literature known complexes with other transition metals. In Chapter 4 the reactivity of several iron(II) complexes with the ligand cyclam and its methylated derivatives, especially tetramethylcyclam (TMC) toward various oxygen species is shown. The successful formations of desired oxido-complexes, which are relevant in multiple enzymatic reactions as key compounds, were also investigated spectroscopically in the low temperature range and mechanistic studies were performed. One example is an iron(II) complex supported by the ligand TMC and a triflate anion in reaction with aqueous hydrogen peroxide. Its possible mechanism based on the measured data is shown with the rate-determining step being the initial addition of H2O2. Furthermore, complexes of the open-chain and guanidine-based ligand DMEG3tren were spectroscopically studied as iron and chromium complexes to obtain a first overview and comparison of different systems and their reactivity.
Keywords: Chemie; Anorganische Chemie; Koordinationschemie; Eisen; Nickel; Sauerstoffaktivierung; Kinetik; ddc:540